Geochemical anomalies in the Lower Silurian shale gas from the Sichuan Basin, China: Insights from a Rayleigh-type fractionation model. (April 2020) - Feng, Ziqi; Hao, Fang; Dong, Dazhong; Zhou, Shangwen; Wu, Wei; Xie, Chen; Cai, Yuwen; Li, Zhixin
Highlights: Composition, δ 13 C, and δ 15 NN2 determined for gas samples from the SW Fuling block. Redox reactions of the carbonaceous material lead to abnormal δ 13 C1 values. Distribution the δ 13 C values suggests effects of diffusion and possible reactions. Abstract: To verify recent single-well data from the Sichuan Basin, we analyzed the molecular and isotopic composition of late-mature Longmaxi shale gases from the southwestern portion of the Fuling block. The gases are highly enriched in methane (>96.1%) and have low C2+ hydrocarbon contents (<0.51%). The gases exhibit a reversal in carbon isotopes (δ 13 C3  < δ 13 C2  < δ 13 C1 ), and their δ 13 C1 values are abnormally enriched (i.e., equal to, or in some cases, more enriched than the associated kerogen). The helium component is typical of crustal genesis from the radiogenic decay of U and Th within the shale, which ranges from 145 ppm to 253 ppm, and its R/Ra ranges from 0.01 to 0.05. The δ 15 NN2 values range from −5.2‰ to −1.1‰, suggesting that the nitrogen was produced from the thermal de-ammoniation of organic matter. At extremely high thermal maturities and geothermal temperatures, shale gases with abnormally enriched δ 13 C1 values can best be explained using the model of Burruss and Laughrey (2010), which invokes a Rayleigh-type isotopic fractionation of ethane as it undergoes redox reactions to form methane and residual carbon in the late-stage (post-oil cracking) generation of methane. The variations in the distribution of δ 13 C1 and δ 13 C2 within the Fuling block imply that fluid-rock interactions related to the CO2 may have occurred, but not to a significant degree, and the cumulative effects of diffusion were also observed. Unraveling the geological processes that create the geochemical anomalies found in these Lower Silurian shale gas samples can provide valuable insight into the late-stage gas generation.